Infectiousness of Sylvatic and Synanthropic Small Rodents Implicates a Multi-host Reservoir of Leishmania (Viannia) braziliensis. - Maria S Andrade; Orin Courtenay; Maria E F Brito; Francisco G Carvalho; Ana Waléria S Carvalho; Fábia Soares; Silvia M Carvalho; Pietra L Costa; Ricardo Zampieri; Lucile M Floeter-Winter; Jeffrey J Shaw; Sinval P Brandão-Filho (Public Library of Science (PLoS), 2015)
BACKGROUND:The possibility that a multi-host wildlife reservoir is responsible for maintaining transmission of Leishmania (Viannia) braziliensis causing human cutaneous and mucocutaneous leishmaniasis is tested by comparative analysis of infection progression and infectiousness to sandflies in rodent host species previously shown to have high natural infection prevalences in both sylvatic or/and peridomestic habitats in close proximity to humans in northeast Brazil. METHODS:The clinical and parasitological outcomes, and infectiousness to sandflies, were observed in 54 colonized animals of three species (18 Necromys lasiurus, 18 Nectomys squamipes and 18 Rattus rattus) experimentally infected with high (5.5 × 10(6)/ml) or low (2.8 × 10(5)/ml) dose L. (V.) braziliensis (MBOL/BR/2000/CPqAM95) inoculum. Clinical signs of infection were monitored daily. Whole animal xenodiagnoses were performed 6 months post inoculation using Lutzomyia longipalpis originating from flies caught in Passira, Pernambuco, after this parasite evaluation was performed at necropsy. Heterogeneities in Leishmania parasite loads were measured by quantitative PCR in ear skin, liver and spleen tissues. RESULTS:All three rodent species proved to establish infection characterized by short-term self-resolving skin lesions, located on ears and tail but not on footpads (one site of inoculation), and variable parasite loads detected in all three tissues with maximum burdens of 8.1 × 10(3) (skin), 2.8 × 10(3) (spleen), and 8.9 × 10(2) (liver). All three host species, 18/18 N. lasiurus, 10/18 N. squamipes and 6/18 R. rattus, also proved infectious to sandflies in cross-sectional study. R. rattus supported significantly lower tissue parasite loads compared to those in N. lasiurus and N. squamipes, and N. lasiurus appeared to be more infectious, on average, than either N. squamipes or R. rattus. CONCLUSIONS:A multi-host reservoir of cutaneous leishmaniasis is indicated in this region of Brazil, though with apparent differences in the competence between the rodent species. The results provide preliminary insights into links between sylvatic and peri-domestic transmission cycles associated with overlaps in the rodent species' ecological niches.